Dampak Penjualan Barang Thrifting Di Indonesia - M Susilo Agung Saputro; Aris Prio Agus Santoso; Nanda Puspitasari Wardoyo; Nurani Sofiyana; Shahnata Putri Dwi Ramadhani (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The thrifting phenomenon has become a rapidly growing trend in Indonesia, especially among the younger generation. Thrifting, or the activity of buying used goods, has a significant impact, especially in economic, environmental and social contexts. This research aims to determine the impact of selling thrifting goods and solutions that can be proposed to overcome the problem of thrifting in Indonesia. The research method uses a literature study approach, the data is then analyzed qualitatively. The research results were obtained directly from the impact of thrifting goods sales in Indonesia, including; The impact on the economy in Indonesia is in the form of lower prices for illegally imported goods compared to local products which can reduce the competitiveness of local business actors, even triggering business closures; Environmental and health impacts in the form of hazardous materials containing bacteria, for example on the skin. Due to low quality and cleanliness it can cause health issues such as scabies and eczema; The impact on economic actors could also be in the form of low local MSME textile production, as well as a drastic reduction in demand for goods and a decline in general competitiveness; The impact on consumers is in the form of easy access to quality goods at more affordable prices from well-known brands.